Environment and earth observation : case studies in India - Hazra, Sugata (Springer remote sensing/photogrammetry., 2017)
This book presents relevant and contemporary research on the remote sensing of landscapes, agriculture & forestry, geomorphology, coasts & oceans, natural hazards and wild habitats. It highlights the application of remote sensing in understanding natural processes and oceanic features, as well as in creating mapping inventories of water resources across different spatial and temporal scales. Recent advances in hyperspectral imaging and high spatial resolution offer promising techniques for exploring various aspects related to the fruitful and cost-effective monitoring of large-scale environments. In the field of forestry and agriculture, the book addresses topics such as terrain analysis, forest management, updating current forest inventories, and vegetation cover type discrimination. It also elaborates delineation of various geo-morphological features of the earth?s surface and natural disasters, and includes a special section on the remote sensing of wild habitats. Readers working in interdisciplinary sectors engaged in remote-sensing-based research benefit from the techniques presented.